Comprehensive mathematical analysis and simulation design of a microwave wireless power transmission system - Meem, Afrin Sultana; Faisal, Abrar; Tarafder, Pulok; Henry, Bukenya (Brac University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.